FACTORS AFFECTING THE DIFFICULTIES OF ECONOMIC LEARNING STUDENTS OF CLASS XI SMA NEGERI 2 WAJO - Hidayat, Neneng; Said, Muh Ihsan; Rahmatullah, Rahmatullah; Inanna, Inanna; Mustari, Mustari (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
Based on the results of research at SMA Negeri 2 Wajo, information was obtained that there are several factors that influence students' learning difficulties in the eyes of students in economic subjects, namely the interest factor, the talent factor, the motivation factor, the learning ability factor, the teacher factor, the friend factor, parent factor. The procedure for this research was carried out by using the classical assumption test and the normality test of the data of the research subject as many as 67 students from class XI IPS 1 and XI IPS 2. The data collection technique used was by giving student questionnaires to SMA Negeri 2 Wajo. Based on the quantitative analysis of the data obtained, it is concluded that the interest factor, talent factor, motivation factor, learning ability factor, teacher factor, friend factor, and parental factor affect learning difficulties at SMA Negeri 2 Wajo.